Needs Analysis Of Master Program Of Physical Education At Singaperbangsa Karawang University - Febi Kurniawan; Resty Gustiawati; Rolly Afrinaldi; Qorry Armen Gemael; Deden Akbar Izzuddin (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
This study was aimed to determine needs of Master Program of Physical Education, Singaperbangsa Karawang University. This research method is descriptive with a survey using a questionnaire. This research was carried out in 2020, the research sample was students and alumni of PJKR Unsika. Analysis of the data used is univariate analysis, and bivariate using the SPPS application. Univariate analysis was performed on each variable to determine the proportion of each questionnaire. Bivariate analysis was conducted to determine the relationship between Respondent Factors and Study Program Factors on the Needs of the Masters Program in Physical Education at Singaperbangsa University. The results of the bivariate data analysis of the respondents' factors were significant, namely because sig. (2 tailed) = 0.000 p < 0.05, it can be concluded that there is a significant relationship between the study program factors and the needs of the Master of Physical Education Program, so many Once alumni who are already working as teachers and not working in the world of education have the desire to continue their education in the Master Program in Physical Education at the University of Singaperbangsa, while for the study program factor, the significant factor is because sig.(2 tailed) = 0.000, p < 0.05, it can be concluded that there is a significant relationship between the study program factors and needs of Master Program in Physical Education at the University of Singaperbangsa so that the University of Singapore is eligible to open a Master Program in Physical Education.